Denture-induced fibromatous hyperplasia - case report - Smiljka Cicmil; Ognjenka Janjić-Pavlović; Mihael Stanojević; Ana Cicmil; Olivera Govedarica; Zorica Stojanović; Jelena Lečić (Биомедицинска истраживања, 2023)
Introduction: Denture-induced fibrous hyperplasia (DFH) is a reactive lesion that occurs as a result of chronic trauma caused by the denture on the oral mucosa. Case report. A female patient, 56 years old, reported to the Specialist Center for Dentistry at the Faculty of Medicine in Foča for the fabrication of complete dentures. She wore previous complete dentures for about 25 years and complained about their age and discoloration. Clinically, both dentures were poorly retained and stabilized by short wings, with pronounced signs of wear. Denture hygiene was poor. Multiple folds of hyperplasic connective tissue were observed in oral cavity upper vestibule mucosa. The lesion folds were pink and firm, corresponding to denture edges. Based on the anamnesis and clinical examination, a temporary diagnosis of denture-induced hyperplasia was made. The patient was informed about clinical condition assessment as well as possible therapeutic procedures and gave written consent to accept the offered therapeutic procedures. She was advised not to wear dentures for four weeks and to maintain proper oral hygiene. After that, the hyperplasia was surgically removed under local anesthesia. A tissue sample was sent for pathohistological analysis. A new pair of total dentures was made. Removed tissue pathohistological examination confirmed the diagnosis: "Epulis fissuratum". Conclusion: Education and regular check-ups are essential for the prevention of DFH. Patients should be given detailed oral and written instructions on oral and denture hygiene maintenance, with special reference to possible changes in oral tissues and the importance of regular follow-ups.
Keywords: oral mucosae lesions; denture-induced hyperplasia; dentures; risk factors